Niche squeeze induced by climate change of the cold-tolerant subtropical montane Podocarpus parlatorei - Quiroga, Maria Paula (2018)
Under changing climates, the persistence of montane subtropical taxa may be threatened as suitable habitats decrease with elevation. We developed future environmental niche models (ENNMs) for Podocarpus parlatorei, the only conifer from southern Yungas in South America, and projected it onto two greenhouse gas concentration scenarios based on 13 global climate models for the years 2050 and 2070. Modelling identified that P. parlatorei is sensitive and restricted to a relatively narrow range of both warm season temperature and precipitation. By the mid-late twenty-first century areas of high suitability for P. parlatorei will not migrate but overall suitability will become substantially reduced across its whole range and surrounding areas. Despite extensive areas in high mountain ranges where the species may encounter thermally optimal conditions to potentially allow upward local migration, these same areas will likely become strongly aridified under future conditions. On the other hand, in lowland locations where rainfall levels will not change substantially (e.g. northern range), excessive warming will likely generate abiotic and biotic restrictions (e.g. competition with lowland species) for this cold-tolerant species. Urgent measures should be developed for the local long-term preservation of the gene pool of the unique conifer that characterizes Yungas forests for reasons of biodiversity conservation and ecosystem services.